Keanekaragaman Jenis Amfibi pada Habitat Terestrial dan Akuatik di KHDTK Hutan Pendidikan Hampangen Kalimantan Tengah : Amphibian Diversity in Terrestrial and Aquatic Habitats in The Hampangen Educational Forest KHDTK Central Kalimantan - Purba, Crysia Lenchiana; Rizal, Moh; Octavianus, Robby; Junaedi, Ajun; Sudomo, M. Fadhil A (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
The purpose of this study was to identify amphibian species in terrestrial and aquatic habitats and to analyze species diversity, species richness and species evenness indices in the Hampangen Educational Forest (KHDTK). The method used was strip transect observation with a transect length of ±400m and a left-right width of 5m. The selection of transects was done using purposive sampling. The results of the study showed that there were 7 species of amphibians found and identified in terrestrial and aquatic habitats from 3 families (Ranidae, Dicroglossidae, Rhacophoridae). The Shannon-Wiener diversity index (H’) for amphibian species in terrestrial habitats was 1.790 (moderate category) and in aquatic habitats was 1.078 (low category). The species richness index for amphibians in terrestrial and aquatic habitats is in the low category, with values of 0.291 and 0.513, respectively. Meanwhile, the species evenness index in terrestrial and aquatic habitats is in the high category, with values of 0.920 and 0.982, respectively. Keywords: amphibians, species diversity, terrestrial, aquatic, KHDTK